Hypothermia blocks β-catenin degradation after focal ischemia in rats - Zhang, Hanfeng; Ren, Chuancheng; Gao, Xuwen; Takahashi, Tetsuya; Sapolsky, Robert M.; Steinberg, Gary K.; Zhao, Heng (Brain research, 2008)
Dephosphorylated and activated glycogen synthase kinase (GSK) 3β hyperphosphorylates β-catenin, leading to its ubiquitin-proteosome-mediated degradation. β-catenin-knockdown increases while β-catenin overexpression prevents neuronal death in vitro; in addition, protein levels of β-catenin are reduced in the brain of Alzheimer's patients. However, whether β-catenin degradation is involved in stroke-induced brain injury is unknown. Here we studied activities of GSK 3β and β-catenin, and the protective effect of moderate hypothermia (30 °C) on these activities after focal ischemia in rats. The results of Western blot showed that GSK 3β was dephosphorylated at 5 and 24 h after stroke in the normothermic (37 °C) brain; hypothermia augmented GSK 3β dephosphorylation. Because hypothermia reduces infarction, these results contradict with previous studies showing that GSK 3β dephosphorylation worsens neuronal death. Nevertheless, hypothermia blocked degradation of total GSK 3β protein. Corresponding to GSK 3β activity in normothermic rats, β-catenin phosphorylation transiently increased at 5 h in both the ischemic penumbra and core, and the total protein level of β-catenin degraded after normothermic stroke. Hypothermia did not inhibit β-catenin phosphorylation, but it blocked β-catenin degradation in the ischemic penumbra. In conclusion, moderate hypothermia can stabilize β-catenin, which may contribute to the protective effect of moderate hypothermia.